Development E- module Based on Flipbook for Increase Ability Students in Learning Layout Cikatri Makeup - Maghfiroh, Anik; Ihsani, Ade Novi Nurul; Purnawirawan, Okta; Saputro, Godham Eko; Tumangger, Mia Hafizah; Afifah, Indah Indi (Jurnal Penelitian Pendidikan, 2025)
Education in the digital era demands increased digital integration in the world of education. This requires innovative learning media that can increase student engagement and achievement. However, this condition also presents challenges and demands for educators to have the ability to integrate information technology interactively during the learning process, so that learning objectives can be achieved optimally. Therefore, learning media are needed that support the learning process both classically and independently. This study aims to develop a flipbook-based e-module as an interactive learning tool for the Makeup course in the Beauty Education Study Program, Semarang State University. This study uses the Research and Development R&D (Research and Development) approach with the ADDIE model, which consists of five stages: analyze, design, development, implementation, and evaluation. Data collection was carried out through interviews, observation sheets, and tests. The validation results using the observation sheet showed an average score of 87.33%, while validation by material experts obtained an average score of 90.66%. Both results indicate that the developed e-module is valid and very feasible to use. The trial using the one group pretest-posttest model resulted in an average pretest score of 58.4% and an average posttest score of 86%. Meanwhile, the results of the student questionnaire showed that the use of the flipbook-based e-module obtained an average score of 77%, which is included in the very feasible category. Based on the results of the validation, trial, and student responses, it can be concluded that the developed flipbook-based e-module meets the criteria of being very valid and feasible to use as a supporting medium in a directed and effective learning process.